A Review On: Lumpy Skin Disease In Cattle (Journal of Pharmaceutical Negative Results, 2022)
The geographical distribution of lumpy skin disease (LSD), an economically important cattle disease caused by a capripoxvirus, has reached an unprecedented extent. It is caused by Lumpy skin disease virus (LSDV), which belongs to the family Poxviridae, with the Neethling strain the prototype. LSDV belongs to the genus Capripoxvirus that includes sheep pox virus and goat pox virus. The original foci of LSD are from Zambia in 1929. LSD is considered as an endemic disease in the African continent. However, the disease has been moved beyond Africa in 1984.Vaccination is the only way to prevent the spread of the infection in endemic and newly affected regions. In the event of an outbreak, selection of the best vaccine is a major challenge for veterinary authorities and farmers. Decision makers need sound scientific information to support their decisions and subsequent actions. The available vaccine products vary in terms of quality, efficacy, safety, side effects, and price. The aim of the present study was to develop a universal real-time PCR assay using man chemistry to cover field, vaccine, and recombinant strains of lumpy skin disease virus isolates.